PSXVI-10 Growth performance, nutrient digestibility, meat quality, blood profiles, and gut health supplemented with Synbiotic Yeast Culture in broiler diets. (7th December 2018) - Sun, H; Kim, K; Zhang, W; Kim, I
Abstract: Yeast culture has been widely used in poultry husbandry as growth promoter in recent years. A total of 576 one-day-old male broilers chickens (Ross 308) with an average initial body weight (BW) of 37 ± 0.51 g were used in a 35 days completely randomized design to evaluate the effect of dietary supplementation of Mixed Yeast Culture (Saccharomyces cerevisiae YJM1592 and Kluyveromyces maxianus TB7258, MYC) on growth performance, nutrient digestibility, meat quality, blood profiles, and gut health. Broilers were randomly allotted to 3 dietary treatments containing: CON, Basal diet; TRT1, CON + 0.1% MYC; TRT 2, CON + 0.2% MYC. There were 12 replicated pens per treatment with 16 broiler chickens per pen. All data were analyzed using GLM procedures of SAS (SAS Inst. Inc., Cary, NC). Orthogonal polynomials were used to assess the linearand quadratic effects oftreatments. On phase 3 and overall period, BWG were linearly increased (P = 0.019, P = 0.002, respectively) with the increase of MYC levels. FCR were linearly decreased (P = 0.017, P = 0.002, respectively) with supplemental levels of MYC during phase 2 and overall period. Digestibility of dry matter (DM) was linearly increased (P = 0.038) in broilers fed MYC diets. Bursa of Fabricius in relative organ weight was linearly increased (P = 0.028) in broilers fed MYC diets. White blood cell (WBC) showed linear and quadratic increase (P = 0.045, P = 0.044, respectively) in the broilers fed MYC diets. Excreta Lactobacillus were linearly increased (P = 0.033) in MYC groups. In conclusion, MYC supplementation in diets improved the growth performance, enhanced the total tract digestibility of DM, modulate the concentrations of WBC and Lactobacillus, influenced the Bursa weight in broiler chickens. This study provided the basis for future research on MYC as a growth promoter in broiler diets.